Using paleoseismology and tephrochronology to reconstruct fault rupturing and hydrothermal activity since c. 40 ka in Taupo Rift, New Zealand. (January 2019) - Loame, Remedy C.; Villamor, Pilar; Lowe, David J.; Milicich, Sarah D.; Pittari, Adrian; Barker, Shaun L.L.; Rae, Andrew; Gómez-Vasconcelos, Martha G.; Martinez-Martos, Manuel; Ries, William F.
Abstract: The Taupo Volcanic Zone (TVZ) in North Island, New Zealand, is the on-land continuation of the Tonga-Kermadec arc formed in the Quaternary at the obliquely convergent boundary of the Pacific and Australian tectonic plates. The central TVZ is a region of intense silicic volcanism and active rifting with a very high heat flux. Within this zone is a dynamic landscape affected by a dense, active fault network, the Taupo Rift. In this rift, the Ngakuru graben hosts fossil hydrothermal systems in an area parallel to numerous active faults including the east strand of Whirinaki Fault that forms a major structure. Using various geoscientific techniques including mapping, stratigraphy, paleoseismic trenching, and tephrostratigraphy, in conjunction with LiDAR-derived DEMs, we reconstruct and date the fault's rupture history along with hydrothermal activity (including silica-sinter development) since c. 40, 000 calendar years ago (40 cal. ka) at a site near Hossack Road called "Meade". Ages for Kawakawa (c. 25.4 cal. ka), Okareka (c. 21.8 cal. ka), Rotorua (c.15.6 cal. ka), Rotoma (c. 9.4 cal. ka), and Taupo (c. 1.7 cal. ka) tephras enabled us to date five identified fault rupture events using the Meade trench excavation. Slip rates of 2.66 ± 0.77 mm/yr (pre-Kawakawa tephra), 0.28 ± 0.04 mm/yr (between c. 25.4 ka and Taupo) and 0.51 ± 0.19 mm/yr (post-Taupo), and the recurrence interval of ∼5500 cal. yr during the last c. 25.4 cal. kyr, all correlate with events of similar ages determined from studies on other trenches on Whirinaki Fault. Intercalated with Tahuna tephra (c. 39.3 cal. ka) and additionally dated at c. 38.9 cal. ka using radiocarbon, the hydrothermal sinter began developing at the Meade site at c. 39 cal. ka and ceased by c. 21.8 cal. ka (marked by Okareka tephra). We examine the causative relationship between fault activity and the development of sinter by comparing the chronology of volcanic eruptions and fault rupturing events with that of sinter formation as recorded in three neighbouring sites, Mangatete, Matthews, and Fitzpatrick. The findings improve understanding of the complex rupture behaviour of faulting and provide evidence for relationships between tectonic and hydrothermal activities, which were additionally influenced by the impacts of climatic change and geomorphic processes on landscape evolution, within the late Quaternary period. The study also exemplifies the unique value of tephrochronology in helping to disentangle complex geological deposits and events in an extremely dynamic part of the Earth's surface (the Taupo Rift). Highlights: An active fault and hydrothermal sinters occur together in the dynamic Taupo Rift, TVZ. We date the fault rupture history and hydrothermal activity ≤40 ka via tephrochronology. Five ruptures occurred: pre-25.4 ka, 25.4–21.8 ka, 15.6–9.4 ka, 9.4–1.7 ka, post-1.7 ka. Sinters were deposited 39–21.8 ka, relating partly to changes of location of heat source. Landscape shaped by combination of fault and hydrothermal activity, LGM-climate change.